Small-scale solar wind density turbulence spectrum from interplanetary scintillation observations - Glubokova, S.K.; Chashei, I.V.; Tyul'bashev, S.A. (Advances in Astronomy and Space Physics, 2012)
The method of determining the angular sizes of compact radio sources and parameters of the plasma turbulence using temporal scintillation power spectra is described and tested. The observations were carried out with the radio telescope BSA of Lebedev Physical Institute at the frequency 111 MHz. Estimates of the angular size and the turbulence parameters are obtained for the strong scintillating source 3C 48 observed during April-May of 2007-2009. During these periods the interplanetary plasma was comparatively quiet.